Re-description and systematic re-appraisal of the genus Kokkocynips Pujade-Villar & Melika, (Hymenoptera: Cynipidae: Cynipini), including new combinations of Nearctic species and the description of a new species from Panama - Nieves-Aldrey, José Luis; Nicholls, James A.; Tang, Chang-Ti; Melika, George; Stone, Graham N.; Pujade-Villar, Juli; Buffington, Matthew; Maldonado, Yurixi; Medianero, Enrique (Zootaxa, 2021)
The monophyly and taxonomic validity of some currently accepted genera of gall wasps in the Cynipini (Hymenoptera: Cynipidae) are being challenged by recent systematic studies. Here we used morphological and molecular data to re-describe and revise the taxonomic limits of the monotypic genus Kokkocynips Pujade-Villar & Melika, previously recorded only from Mexico.                We describe a new species from Panama, Kokkocynips panamensis Medianero & Nieves-Aldrey, reared from galls on Quercus salicifolia Neé, and add new records from Mexico for the type species of the genus K. doctorrosae Pujade-Villar. Six Nearctic species, Dryocosmus rileyi (Ashmead, 1896), D. imbricariae (Ashmead, 1896), D. coxii (Basset, 1881), D. deciduus (Beutenmueller, 1913), Callirhytis difficilis (Ashmead, 1887) and C. attractans (Kinsey, 1922) are transferred to Kokkocynips. Species of Kokkocynips are associated only with red oaks (Quercus section Lobatae (Fagaceae)) and are distributed in the Nearctic and Neotropical regions, from Canada through Mexico and Panama. Taxonomic limits of Kokkocynips are discussed in light of the molecular phylogenetic relationships of the studied species. Diagnostic characters, gall description, distribution, and biological data of Kokkocynips species are given, including a key for the identification of the asexual generations of seven species.